Kepemimpinan Modern: Konsep Dan Implementasi Perspektif Hukum - Nursamsi Nursamsi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Leadership is not just a position or position, but rather a set of skills, attitudes and behaviors that enable someone to influence others positively. In this article, the author will explain why leadership has become so important in the modern era and its main role in facing various challenges faced by organizations and society in general. The importance of leadership lies in its ability to guide, manage and move people towards achieving common goals.